“Desarrollo de una aplicación web y móvil empleando prácticas ágiles para la gestión de la asociación de árbitros profesionales de fútbol de Cotopaxi.” - Guamushig Chicaiza, Tania Lisseth (2023)
This titling project was carried out in the Association of Professional Soccer Referees of Cotopaxi located in the city of Latacunga, province of Cotopaxi, where through the application of field research techniques, such as surveys, interviews and observation, some limitations were identified in the management of the information control processes of the referees, clients and sporting events, on the other hand, it lacks computer applications for sports management for the referees, these actions are generated manually in sheets and agendas, which causes a greater investment of resources and time. For this reason, the generation of a technological proposal is required for the development of a web and mobile application for the "Association of Professional Soccer Referees of Cotopaxi".